2007
DOI: 10.1111/j.1477-8947.2007.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of renewable soil fertility replenishment technologies in the southern African region: Lessons learnt and the way forward

Abstract: Low soil fertility is one of the most important biophysical constraints to increasing agricultural productivity in sub-Saharan Africa. Several renewable soil fertility replenishment (RSFR) technologies that are based on nutrient re-cycling principles have been developed in southern Africa. Some success stories have been recorded (e.g. nitrogen-fixing legumes), but the adoption of RSFR technologies has generally lagged behind scientific advances thereby reducing the potential impacts of the technologies. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
90
1
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 117 publications
(105 citation statements)
references
References 47 publications
10
90
1
4
Order By: Relevance
“…The results of this study suggest in line with earlier research [19,32] that the availability of information and training are important for farmers' decisions to start testing a new technology whereas socio-cultural issues becomes an additional challenge for a continuation beyond the testing phase leading to adoption of the technology [16][17][18][19][20]. This study also demonstrates the importance of governance and collaboration for the adoption process, the need to integrate project activities and capacity building into local structures to provide leverage in adaptation, adoption, and scaling up.…”
Section: The Process Of Learning Adaption and Adoption: Synthesizingsupporting
confidence: 83%
See 4 more Smart Citations
“…The results of this study suggest in line with earlier research [19,32] that the availability of information and training are important for farmers' decisions to start testing a new technology whereas socio-cultural issues becomes an additional challenge for a continuation beyond the testing phase leading to adoption of the technology [16][17][18][19][20]. This study also demonstrates the importance of governance and collaboration for the adoption process, the need to integrate project activities and capacity building into local structures to provide leverage in adaptation, adoption, and scaling up.…”
Section: The Process Of Learning Adaption and Adoption: Synthesizingsupporting
confidence: 83%
“…The above results show, in line with Pollini [16], Ajayi et al [19], and Johansson et al [32], that the explanation to the contradictions similar to those found in this study often lies in the institutional and social-cultural contexts and requires a deeper understanding of the dynamics of the adoption processes of the respective study areas. In the decision to continue using a technology or not lies not only biophysical, technical and economic considerations, the prevailing socio-cultural contexts such as customs, obligations, beliefs and supportive governance are also important.…”
Section: The Process Of Learning Adaption and Adoption: Synthesizingsupporting
confidence: 79%
See 3 more Smart Citations